Datataxa: a new script to extract metadata sequence information from GenBank, the Flora of Bajío as a case study - Eduardo Ruiz-Sanchez; Carlos Alonso Maya-Lastra; Victor W. Steinmann; Sergio Zamudio; Eleazar Carranza; Rosa María Murillo; Jerzy Rzedowski (Botan‪ical Sciences, 2019)
Background: GenBank is a public repository that houses millions of nucleotide sequences. Several software have been developed to extract information stored in GenBank. However, none of them are useful to extract and organize GenBank accession based on metadata. We developed a new script called Datataxa, which works to mine GenBank information. The checklist of the Flora del Bajío y de Regiones Adyacentes (FBRA) was used as a case study to apply our script.